1991
DOI: 10.3171/jns.1991.75.1.0077
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome: surgical treatment using the Paine retinaculatome

Abstract: The operative technique for the relief of carpal tunnel syndrome has remained controversial. This report presents the results of 445 patients or 577 hands operated on using a transverse technique that varies little from that described by Paine and Polyzoidis. The patients were followed for 9 months to 3 years. In addition to the data received from follow-up visits, a questionnaire was sent to each patient for evaluation of their results. All surgery was performed under local anesthesia, sometimes with intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Some surgical outcome studies that include NCSnegative patients failed to provide a breakdown of outcome by NCS result. 26 At least two studies have suggested that, in patients with normal NCS results, surgical treatment may lead to unfavorable outcomes, 2,12 and a recent report indicated that surgical outcome is more favorable in patients with longer preoperative median latencies. 6 In summary, we found that NCS results provide independent information not fully predictable from clinical variables alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgical outcome studies that include NCSnegative patients failed to provide a breakdown of outcome by NCS result. 26 At least two studies have suggested that, in patients with normal NCS results, surgical treatment may lead to unfavorable outcomes, 2,12 and a recent report indicated that surgical outcome is more favorable in patients with longer preoperative median latencies. 6 In summary, we found that NCS results provide independent information not fully predictable from clinical variables alone.…”
Section: Discussionmentioning
confidence: 99%
“…Phalen advocated bilateral carpal tunnel releases, performed at least 1 month apart to minimize incapacitation and improve the chance of recovery [29,31]. Other reports have described success with simultaneous bilateral procedures [2,5,25,26]. Pagnanelli and Barrer reported that simultaneous releases, using the Paine retinaculatome, relieved symptoms in 94% of 228 patients with bilateral symptoms [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although Pagnanelli and Barrer [17] reported no recurrent thenar branch injuries after CTR surgery via a blind technique using the retinaculotome, we remain concerned that the rare aberrant course of the recurrent thenar motor branch can predispose it to be injured in any blind procedure. Median and ulnar nerve transection injuries along with nerve contusion and vascular injuries with both the uniportal and two-portal ECTR techniques have been reported.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous reports have documented that sectioning of the TCL by any method leads to excellent results in patients with CTS. [1,5,7,8,17,26,27] Previous reports have described endoscopic CTR (ECTR) surgery as a technically demanding procedure with a significant learning curve. [2,6,7,9,15,22,23] The immediate question that arises is: why make a simple surgery more difficult?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation